The second clinical survey of the population-based study on health and living conditions in regions with Sami and Norwegian populations – the SAMINOR 2 Clinical Survey: Performing indigenous health research in a multiethnic landscape - Broderstad, Ann Ragnhild; Hansen, Solrunn; Melhus, Marita (Scandinavian Journal of Public Health, 2019)
Background - Globally, there is a huge lack of relevant research about widespread lifestyle diseases and living conditions in indigenous communities. Northern and Middle Norway have a history of multiple ethnic groups and the Sami has been acknowledged as the indigenous people of Norway by the Norwegian State. The SAMINOR 2 Clinical Survey, a part of the SAMINOR Study, was carried out to provide health information about the Sami population in Norway. Methods - The cross-sectional population-based SAMINOR 2 Clinical Survey consists of both questionnaires and a clinical examination performed in 10 municipalities during 2012–2014. Results - In total, 6004 men and women (participation rate 48%) aged 40–79 years took part in this study. In inland Finnmark, the Sami are in the majority (80–90%) as opposed to the coastline of Troms and Nordland, where the Sami population form a minority (20%). More women than men participated (54% versus 43%, respectively). Obesity was prevalent in this sample and a high mean glycated haemoglobin was observed. Conclusions - This article describes the methods and data collection of the SAMINOR 2 Clinical Survey and presents some characteristics of the sample. The definition of ethnic groups is a core question in the survey and includes several criteria. To ensure that indigenous values and priorities are reflected in the research themes, we recommend that future research projects be directed in close collaboration with the Sami Parliament and the local communities.